Variation in follow-up for children born very preterm in Europe - Seppänen, AV (2023)
Background Children born very preterm (<32 weeks of gestation) face high risks of neurodevelopmental and health difficulties compared with children born at term. Follow-up after discharge from the neonatal intensive care unit is essential to ensure early detection and intervention, but data on policy approaches are sparse. Methods We investigated the characteristics of follow-up policy and programmes in 11 European countries from 2011 to 2022 using healthcare informant questionnaires and the published/grey literature. We further explored how one aspect of follow-up, its recommended duration, may be reflected in the percent of parents reporting that their children are receiving follow-up services at 5 years of age in these countries using data from an area-based cohort of very preterm births in 2011/12 (N = 3635). Results Between 2011/12 and 22, the number of countries with follow-up policies or programmes increased from 6 to 11. The policies and programmes were heterogeneous in eligibility criteria, duration and content. In countries that recommended longer follow-up, parent-reported follow-up rates at 5 years of age were higher, especially among the highest risk children, born <28 weeks’ gestation or with birthweight <1000 g: between 42.1% and 70.1%, vs. <20% in most countries without recommendations. Conclusions Large variations exist in follow-up policies and programmes for children born very preterm in Europe; differences in recommended duration translate into cross-country disparities in reported follow-up at 5 years of age.